CD14+ Cells with the Phenotype of Infiltrated Monocytes Consist of Distinct Populations Characterized by Anti-inflammatory as well as Pro-inflammatory Activity in Gouty Arthritis - Jeong, Ji Hye; Hong, Seokchan; Kwon, Oh Chan; Ghang, Byeongzu; Hwang, Inseok; Kim, Yong-Gil; Lee, Chang-Keun; Yoo, Bin (Frontiers in Immunology, 2017)
It has been suggested that inflammasome-mediated IL-1β production in monocytic cells is responsible for the acute inflammatory response in gouty arthritis. However, phenotypical and functional analyses of monocytes during gouty arthritis have yet to be conducted. Therefore, we investigated the characteristics of monocytes/macrophages in the synovial fluid cells of patients with acute gout. The number and frequency of monocytes/macrophages in the synovial fluid mononuclear cells (SFMCs) of patients was examined. The expression of markers for monocyte recruitment and tissue-resident macrophages, the production of pro-inflammatory and anti-inflammatory cytokines, and phagocytosis were analyzed in the monocytes/macrophages of patients with acute gout attacks. The number and frequency of CD14+CD3−CD19−CD56− monocytes/macrophages was markedly increased in the SFMCs of patients with gout compared to those of patients with rheumatoid arthritis (RA). CD14+ cells showed the phenotypes of infiltrated monocytes rather than tissue-resident macrophages, characterized by a high expression of CCR2, MRP8, and MRP14, but a low expression of MERTK and 25F9. These cells had the capacity to produce pro-inflammatory cytokines such as TNF-α and IL-1β after stimulation with lipopolysaccharides. In addition, anti-inflammatory features, including CD163 expression and IL-10 production from CD14+ cells, were significantly higher in patients with gout than in those with RA. CD14+ cells with phenotype of M2 macrophages had high phagocytic activity for monosodium urate crystals. Thus, our results indicate that monocytes/macrophages from patients with gout have the phenotype of infiltrated monocytes, and these cells consist of different populations characterized by anti-inflammatory activities as well as pro-inflammatory functions.